Dynamic evolution of left ventricular strain and microvascular perfusion assessed by speckle tracking echocardiography and myocardial contrast echocardiography in diabetic rats: Effect of dapagliflozin - Liu, Juan; Wang, Yixuan; Zhang, Jun; Li, Xin; Tan, Lin; Huang, Haiyun; Dai, Yang; Shang, Yongning; Shen, Ying (Frontiers in Cardiovascular Medicine, 2023)
Background This experimental study aimed to determine the dynamic changes in myocardial strain and microvascular perfusion in diabetic rats by comprehensive echocardiography while evaluating the effect of dapagliflozin (DAPA). Materials and methods Male Sprague–Dawley rats (n = 128) were randomly divided into four groups based on the presence or absence of a high-fat diet and streptozotocin-induced diabetes with or without DAPA treatment (n = 32/group). Serial conventional ultrasound, two-dimensional speckle tracking echocardiography (2D-STE) and myocardial contrast echocardiography (MCE) were performed at 2, 4, 6, and 8 weeks, and left ventricular global longitudinal strain (GLS), myocardial blood flow velocity (MBFV), myocardial blood flow (MBF), and myocardial blood volume (MBV) were determined. All animals were sacrificed immediately after the last echo measurement for histopathological assessment. Results Despite similar conventional Doppler-echo indexes among the groups at 2, 4, 6, and 8 weeks (p > 0.05), left ventricular GLS, MBFV, MBF, and MBV were decreased at 8 weeks in diabetic rats (p < 0.05) as detected by both 2D-STE and MCE. These indexes were significantly improved at 6 and 8 weeks after treatment with DAPA for diabetic rats (p < 0.05), reaching similar values observed in non-diabetic controls. DAPA treatment was associated with increased myocardial vacuolization and microvessel density and reduced interstitial fibrosis in diabetic rats. Conclusions Combined 2D-STE and MCE is sensitive for detecting left ventricular deformity and impaired microvascular perfusion in prediabetes and the early stage of diabetes mellitus. DAPA exerts a beneficial effect on protecting myocardial perfusion in diabetic rats.